Determination the Concentration of the Radon in some Drinking Bottled Water in Baghdad using LR-115 Detector (Baghdad Science Journal, 2012)
In the present study ten samples of bottled water from Baghdad conservative were taken to measure the concentration of radon gas by using nuclear track detector LR-115.The result obtained are varying from(0.033)to(0.007)pCi.l-1and these values are very low than the allowed limits (5) pCi.l-1, and specific activity from bottled water has been calculated which was vary from (0.00027)to(0.00126) Bq.l-1 and these values are very low than allowed limits (0.0123) Bq.l-1 that mean the bottled water was treated with good treatment to decrease the side effect of radon